Generalized ILVEN or Blaschkoid Psoriasis: A Persistant Dilemma - Apurva Kaushal; Pratik Gahalaut; Nitin Mishra; Madhur Kant Rastogi (Nepal Journal of Dermatology, Venereology & Leprology)
A 24-year-old man presented with itchy verrucous, scaly red-brown papules, & linear plaques distributed in a blaschkoid pattern all over the body since last 20 years associated with itching. A skin biopsy was consistent with ILVEN (inflammatory linear verrucous epidermal nevus). Histopathologically, it can be difficult to distinguish it from linear psoriasis. It may respond to conventional anti-psoriatic therapies like potent topical corticosteroids applied under occlusion, or systemic treatments like acitretin.